Self‐Templated Formation of Pt@ZIF‐8/SiO2 Composite with 3D‐Ordered Macropores and Size‐Selective Catalytic Properties. Issue 12 (17th September 2018) - Tian, Panliang; Shen, Kui; Chen, Junying; Fan, Ting; Fang, Ruiqi; Li, Yingwei
Abstract: Metal–organic frameworks (MOFs) and related derivatives have attracted significant research attention due to their potential applications in a variety of fields. However, it remains challenging to fabricate MOF‐based composites into multidimensional structures, especially to endow them with ordered structures. Here, a facile strategy is developed for the preparation of Pt@ zeolitic imidazolate frameworks (ZIF)‐8/SiO2 composite with 3D‐ordered macroporous (3DOM) structure (denoted as 3DOM‐Pt@ZIF‐8/SiO2 ) by the in situ self‐templated transformation of Pt/ZnO/SiO2 composite with 3DOM structure (denoted as 3DOM‐Pt/ZnO/SiO2 ), which is prepared by a nanocasting method with face‐centered cubic (fcc) polystyrene spheres as the template. The sampling analysis at various crystallization times confirms the detailed dissolution–precipitation process from 3DOM‐Pt/ZnO/SiO2 to 3DOM‐Pt@ZIF‐8/SiO2, in which Pt nanoparticles (NPs) are fully encapsulated into the 3DOM framework of ZIF‐8/SiO2 by a continuous ZIF‐8 shell in the surface. Besides, it is found that choosing suitable volume ratio of N, N ‐dimethylformamide (DMF):H2 O and SiO2 content is crucial to induce the in situ nucleation and growth of continuous ZIF‐8 shell on the 3DOM structure and also to prevent the 3DOM structure from collapsing. Crucially, the obtained 3DOM‐Pt@ZIF‐8/SiO2 shows high size‐selective catalytic properties for the hydrogenation of n ‐hexene and cis ‐cyclooctene due to the molecular sieve effect of ZIF‐8 shell on the framework. Abstract : A facile self‐templated strategy is developed for the encapsulation of Pt nanoparticles within zeolitic imidazolate frameworks (ZIF)‐8/SiO2 with 3D‐ordered macroporous (3DOM) structure by in situ transformation of Pt/ZnO/SiO2 with 3DOM structure based on a dissolution–precipitation mechanism. The obtained 3DOM‐Pt@ZIF‐8/SiO2 exhibits steady size‐selective catalytic properties for the hydrogenation of n ‐hexene and cis ‐cyclooctene.